126 A Student Pilot for A Feasibility Study of the Theoretical 3S Trial (SPFT3S): GP and Ethics Committee Members Questionnaire. (16th March 2021) - Brown, L; Foster, R; Dodd, M; McCormack, T
Abstract: Introduction: Emerging research suggests that statin use for primary prevention in people without diabetes aged 75 and older has no benefit. This study aims to determine the feasibility of the theoretical Stop Statin Study (3S), a double-blind randomised controlled trial carried out in general practice, which would test this hypothesis. 50% of trial patients would stop taking statins for 5 years in an event driven study. The questionnaires aim to identify the attitudes of general practitioners (GPs) and ethics committee members (ECMs) regarding stopping statins for 5 years in patients aged 75 and older without diabetes or history of cardiovascular disease and their willingness to allow patients to participate in the 3S study. Method: Questionnaires comprised of 6 questions were designed. 4 students distributed the questionnaire and it was completed by 19 GPs based at 8 practices in the North-East of England. 31 ECMs (12 expert and 19 lay) responded by email. Results: 95% of GPs who completed the survey would agree to their patients participating in the theoretical study with 47% of GPs indicating that their willingness to participate in the study is patient dependent. 95% of GPs would also consider stopping statins in this population group if sufficient research had been carried out or if the guidelines were changed. 42% of GPs have a negative attitude to prescribing statins in this population group. All the ECMs would approve the study, citing over-prescribing and polypharmacy as their reason. Conclusions: The majority of GPs will participate in the theoretical 3S study, if their patients are willing to participate. There is already a negative perception amongst GPs towards the use of statins in elderly people without disease. The 3S study appears to be feasible from the GP and ethics perspective but would require a larger feasibility study.